Fetal Sacrococcygeal Teratoma: A Case Report of a Giant Tumor with an Excellent Outcome - Kornete, Anna; Bokucava, Diana; Vedmedovska, Natalija (Acta medica Lituanica, 2023)
Sacrococcygeal teratoma (SCT) occurs in approximately 1 per 20,000–40,000 births and is the most frequently encountered fetal teratoma, with 75% of cases observed in female fetuses. SCT can be detected on ultrasound as early as the first trimester, presenting as a large mass originating from the sacrococcygeal area, with or without an intrapelvic component. The prenatal course for most fetuses with SCT is generally uneventful, with only a few cases experiencing obstetric and fetal complications. We present the case of a 19-year-old woman who was in good health and had no relevant family or medical history. She was gravida 2 and para 1. During the first trimester scan, an examination revealed a heterogeneous mass in the presacral area with a predominantly multicystic appearance, measuring 12 mm in diameter. At 21+6 weeks of gestation, the Type 2 fetal SCT showed an increase in volume with the size of 49×37×36 mm and contiune to increase in size. The male fetus was delivered by elective Cesarean section at 38 weeks of gestation. The resection of the tumor and coccyx was performed when the newborn was 7 days old. The tumor measured 190×160×100 mm and weighed 1100 g. Pathological examination confirmed the diagnosis of a mature teratoma (Grade 0), and the resection margins were negative. Our case report highlights a fetus with a large and rapidly growing SCT, yet the outcome was excellent.
Keywords: sacrococcygeal teratomas; prenatal diagnostic; vascular index; alpha-fetoprotein